A minor role of CD4+ T lymphocytes in the control of a primary infection of cattle with Mycoplasma mycoides subsp. Mycoides - Sacchini, F.; Naessens, Jan; Awino, Elias; Heller, M.; Hlinak, A.; Haider, W.; Sterner-Kock, Anja; Jores, Joerg (Springer, 2011)
Contagious bovine pleuropneumonia (CBPP), caused by Mycoplasma mycoides subsp. mycoides, is an important livestock disease in Africa. The current control measures rely on a vaccine with limited efficacy and occasional severe side effects. Knowledge of the protective arms of immunity involved in this disease will be beneficial for the development of an improved vaccine. In previous studies on cattle infected with M. mycoides subsp. mycoides, a correlation was detected between the levels of mycoplasma-specific IFN-γ-secreting CD4+ T lymphocytes and reduced clinical signs. However, no cause and effect has been established, and the role of such cells and of protective responses acquired during a primary infection is not known. We investigated the role of CD4+ T lymphocytes in CBPP by comparing disease patterns and post mortem findings between CD4+ T cell depleted and non-depleted cattle. The depletion was carried out using several injections of BoCD4 specific murine monoclonal antibody on day 6 after experimental endotracheal infection with the strain Afadé. All cattle were monitored clinically daily and sacrificed 28-30 days post-infection. Statistically significant but small differences were observed in the mortality rate between the depleted and non-depleted animals. However, no differences in clinical parameters (fever, signs of respiratory distress) and pathological lesions were observed, despite elimination of CD4+ T cells for more than a week. The slightly higher mortality in the depleted group suggests a minor role of CD4+ T cells in control of CBPP.